Short Communication: Notes on a new distribution record of the Critically Endangered Sunda Pangolin (Manis javanica) in Sabah, Malaysian Borneo - Jephte Sompud; Nurhidayah Sahar; Carmen Adros; Evelyn Richard; Cynthia Boon Sompud (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sompud J, Sahar N, Adros C, Richard E, Sompud CB. 2023. Short Communication: Notes on a new distribution record of the Critically Endangered Sunda Pangolin (Manis javanica) in Sabah, Malaysian Borneo. Biodiversitas 24: 975-981. Sunda pangolin is a Critically Endangered species. The species used to be widespread in Sabah, but its presence has become very scarce due to poaching and illegal trade. For the past decade, there have been individual reports of the distribution of the Sunda pangolin in Sabah. The reports of the locality of the Sunda Pangolin were mainly from the eastern part of Sabah, where large and contiguous forests exist. More comprehensive information on the distribution of the Sunda pangolin is needed to pave ahead with the species conservation and law enforcement to curb poaching and its illegal trade. This study presents a new distributional record of Sunda pangolin in Sabah. The evidence of the new distribution was obtained during field research at SFERA@UMS within the Universiti Malaysia Sabah Hill, Kota Kinabalu, from 10 October to 8 December 2022. Additional evidence was found through citizen science. Based on the track and signs, camera trap image, and the reports from citizen science, we conclude that the Sunda pangolin exists in UMS forest, and at least two individuals have been reported. There are no published reports on the presence of the Sunda pangolin before this. The study also shows how vital citizen science is in biodiversity conservation.